2013
DOI: 10.1371/journal.pone.0072811
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Genetic Diversity of Staphylococcus aureus Causing Bloodstream Infection in Shanghai, 2009-2011

Abstract: Objectives Staphylococcus aureus or methicillin-resistant Staphylococcus aureus (MRSA) has been an important pathogen causing bloodstream infections. Our study aimed to investigate the epidemiological and genetic diversity of clinical S. aureus isolates from patients with bloodstream infection in four hospitals of Shanghai from 2009 to 2011.MethodsA collection of S. aureus isolates causing bloodstream infection from four hospitals in the central part of Shanghai was carried out. Antimicrobial susceptibility te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
28
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 24 publications
(36 reference statements)
10
28
2
Order By: Relevance
“…CC5 (S. aureus: 44/120, 36.7%; MRSA: 37/53, 69.8%) was the dominant clone among patients with SAB at Ruijin Hospital in Shanghai from 2013 to 2018 in this study, slightly different from our previous research conducted in Shanghai from 2009 to 2011 that CC8 (ST239) might be more common among patient with SAB before 27 . However, shifts may be occurring in the molecular epidemiology of S. aureus and MRSA among patients with bloodstream infections.…”
Section: Discussioncontrasting
confidence: 99%
“…CC5 (S. aureus: 44/120, 36.7%; MRSA: 37/53, 69.8%) was the dominant clone among patients with SAB at Ruijin Hospital in Shanghai from 2013 to 2018 in this study, slightly different from our previous research conducted in Shanghai from 2009 to 2011 that CC8 (ST239) might be more common among patient with SAB before 27 . However, shifts may be occurring in the molecular epidemiology of S. aureus and MRSA among patients with bloodstream infections.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, STs associated with both healthcare (ST239 and ST22) and community (ST80 and ST8) infections were found in MRSA strains that were epidemiologically defined as HA and CA. As reported in a previous study in China (Chen et al., ), majority of HA‐MRSA strains were belonged to the epidemic clones ST239. Consistently in this study, ST239 was the predominant lineage among HA‐MRSA strains (60%), whereas it was also detected among CA‐MRSA (26.1%) as was reported in a recent study carried out in China (Xie et al., ).…”
Section: Discussionsupporting
confidence: 70%
“…Different from our findings, some studies conducted in China and India had shown higher rates of MRSA isolates [7,8], whereas in Brazil the resistance rate has remained around 40% [1]. Comparing the results obtained with the susceptibility test for 14 antimicrobials from isolates from the two hospitals, it was possible to detect more MRSA isolates causing BSI in hospital 2 than in hospital 1.…”
contrasting
confidence: 99%